Stawki podatków dochodowych jako czynnik rozwoju MŚP - kierunki zmian - Pohulak-Żołędowska, Elżbieta (Income Tax Rates - a Significant Factor Affecting SMEs' Development: Directions of the Change, 2005)
Income tax rates have a special meaning for SMEs' development. The rates imposed onto the enterprise's income might define its investing ability. Along with the 21st century some important changes in tax systems began. For the income taxes the changes mean mainly "getting simpler". As Irish or British experiences show the simplicity of income taxes brings good results in enterprises' development. Naturally the tax rate is only one of the elements having an influence on the process. In the article the author shows the tendencies in the income tax rates changes and analyzes their usefulness for SMEs' development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 357-364